TMIC-39. DEVELOPMENT OF CD11b TRACER FOR THE IMMUNE PET IMAGING IN GLIOBLASTOMA MODEL - COULD BE A GAME CHANGER FOR IMMUNOTHERAPY APPROACHES. (11th November 2019) - Nigam, Shubhanchi; McCarl, Lauren; Kumar, Rajeev; Anderson, Carolyn; Edwards, Barry; Kohanbash, Gary
Abstract: Glioblastoma is a lethal brain tumor, heavily infiltrated by tumor-associated myeloid cells (TAMCs). As up to 30% of a glioma cellular mass may be attributed to immunosuppressive myeloid cells, including myeloid-derived suppressor cells (MDSCs) and tumor-associated macrophages (TAMs). TAMCs impede natural and immunotherapy-driven anti-tumor responses, they are a high-priority and promising therapeutic target currently being evaluated in clinical trials. Multiple preclinical and clinical trials have attempted to target these cells, however monitoring of biologic responses to therapy remains a challenge. Quantifying real time status of MDSCs and TAMs at the tumor site using non-invasive immunoPET could improve therapeutic response and allow for better patient stratification and monitoring of targeted treatment responses. TAMCs highly expressed the cell surface marker, integrin CD11b (Mac-1, αMβ2) and may be a highly effective imaging target for immunoPET strategies. The human/mouse cross-reactive anti-CD11b antibody (clone M1/70) was radiolabeled with 89 Zr for PET imaging. PET/CT imaging, with or without a blocking dose of anti-CD11b Ab, was performed in mice bearing established orthotopic syngeneic GL261 gliomas. Flow cytometry and histology in tissues collected from post-imaging biodistribution validated targeting of CD11b + MDSCs and TAMs. There was significant Zr-89-anti-CD11b Ab uptake in the tumor ipsilateral right brain (SUVmean = 2.6 ± 0.24) compared to contralateral left brain (SUVmean = 0.6 ± 0.11). Blocking with 10-fold lower specific activity 89 Zr-anti-CD11b Ab reduced the SUV in right brain with (SUVmean = 0.11 ± 0.06). Immune rich organs spleen and lymph nodes showed high uptake. These results correlated with biodistribution analysis. CD11b expression in the right and left brain were validated using flow cytometry, H&E and IHC, showing high CD11b expression in the right brain. Imaging TAMs and MDSCs with 89 Zr-labeled anti-CD11b Ab targeting was validated in a mouse model of malignant gliomas, demonstrating the feasibility of monitoring immune response during immunotherapy.